Immunodominant Antigens of Leishmania chagasi Associated with Protection against Human Visceral Leishmaniasis - Abanades, Daniel R.; Arruda, Leonardo V.; Arruda, Elaine S.; Pinto, Jose Roberto A. S. [UNESP]; Palma, Mario Sergio [UNESP]; Aquino, Dorlene; Caldas, Arlene J.; Soto, Manuel; Barral, Aldina; Barral-Netto, Manoel (Public Library Science, 2012)
Background: Protection and recovery from visceral leishmaniasis (VL) have been associated with cell-mediated immune (CMI) responses, whereas no protective role has been attributed to humoral responses against specific parasitic antigens. In this report, we compared carefully selected groups of individuals with distinct responses to Leishmania chagasi to explore antigen-recognizing IgG present in resistant individuals.Methodology and Principal Findings: VL patients with negative delayed-type hypersensitivity (DTH) were classified into the susceptible group. Individuals who had recovered from VL and converted to a DTH+ response, as well as asymptomatic infected individuals (DTH+), were categorized into the resistant group. Sera from these groups were used to detect antigens from L. chagasi by conventional and 2D Western blot assays. Despite an overall reduction in the reactivity of several proteins after DTH conversion, a specific group of proteins (approximately 110-130 kDa) consistently reacted with sera from DTH converters. Other antigens that specifically reacted with sera from DTH+ individuals were isolated and tandem mass spectrometry followed by database query with the protein search engine MASCO were used to identify antigens. The serological properties of recombinant version of the selected antigens were tested by ELISA. Sera from asymptomatic infected people (DTH+) reacted more strongly with a mixture of selected recombinant antigens than with total soluble Leishmania antigen (SLA), with less cross-reactivity against Chagas disease patients' sera.Significance: Our results are the first evidence of leishmania proteins that are specifically recognized by sera from individuals who are putatively resistant to VL. In addition, these data highlight the possibility of using specific proteins in serological tests for the identification of asymptomatic infected individuals.